Good governance in Malaysian public higher learning institutions:Special reference to International Islamic University Malaysia - Abd Ghadas, Zuhairah Ariff; Hassan, Halyani (2008)
The higher education industry is in the knowledge business, both creating knowledge through research and transferring knowledge to students. The conventional view on the major role of a higher education institution is always educating students but there are many institutions, particularly the research-oriented universities which contended that the major role of higher education industry should be to generate new knowledge through research activities. According to the statistics published by Malaysian Department of Census (DOS) in year 2000, the education industry combined with the health industry are the main actors in the services sector (98.6 percent).This data illustrates the main role of higher education institutions as one of the corporate actors in Malaysia. For the public higher learning institutions, the notion of doing business may not be appropriate as they were established to generate professional human capital for the country. On the other hand, by year 2010, all Malaysian public higher learning institutions are expected to generate their own earnings to cover at least thirty percent of its expenditure and this obviously requires some entrepreneurship in the University. In short, there is no escape for public universities from entering the corporate zone! This paper aims to look into the application of corporate governance/good governance agenda in IIUM, which is in a unique position, being a public higher learning institution and at the same time having the status of a company.